Adsorption of 4-chlorophenol by wheat straw biochar and its regeneration with persulfate under microwave irradiation. Issue 4 (August 2021) - Shen, Tianyao; Wang, Peng; Hu, Limin; Hu, Qi; Wang, Xiaojing; Zhang, Guangshan
Abstract: Adsorption is an efficient technology for contaminant removal in water. However, the adsorbent cost restricts its development, and an eco-friendly treatment is needed for exhausted adsorbents. Wheat straw was utilized as the raw material, ZnCl2 was used as the modifier to prepare modified biochar (BC), and BC was applied to adsorb 4-CP in an aqueous phase. The surface area of BC increased from 1.84 to 234.2 m 2 ·g -1, and the saturated adsorption capacity of 4-CP reached 111.0 mg·g -1 . In the regeneration process, a microwave irradiation (MW)-BC-peroxydisulfate (PDS) system was proposed. The TOC removal reached 98% after 30 min at 90 °C, and the PDS activation rate and dechlorination rate also approached 81.24% and 97%, respectively. The MW-BC/PDS system could regenerate the exhausted BC. After 4 cycles, the regeneration efficiency and 4-CP removal remained at 80% and 60%, respectively, higher than those of water wash regeneration (below 30%). SO4 -· and · OH played a significant role in 4-CP degradation by electron paramagnetic resonance (EPR) and quenching experiments. High temperature and appropriate PDS addition (PDS/BC = 3/2, mass ratio) positively affected dechlorination. The idea of adsorption enriched pollutants mineralized by oxidation regeneration was proposed, which could remove pollutants thoroughly and reduce the cost through reutilization. Graphical Abstract: Schematic representation of 4-chlorophenol (4-CP) removal with adsorption enrichment by modified biochar (BC) and regeneration with peroxydisulfate (PDS) addition under microwave irradiation (MW). Based on electron paramagnetic resonance (EPR) detection, MW and BC's coupling could enhance the PDS activation process of generating SO4 -· and · OH. Quenching experiments found that SO4 -· was the dominant radical in 4-CP degradation. After regeneration, pristine BC can be used for a new round of adsorption. ga1 Highlights: Modified biochar showed a large surface area and high adsorption capacity. The biochar adsorption mechanism for 4-CP removal was studied. Eco-friendly MW-BC/PDS can regenerate biochar with high efficiency. SO4- · and · OH played a major role in the organic pollutant oxidation process. Adsorption-regeneration overcomes the volume limitation of the MW-reactor.